A radio program introducing local Chinese rock music. - Lee, Kay Lin. (2009)
A 25 to 30 minute one-off episode Radio Program in Mandarin introducing the local Chinese Rock Music scene. In this program, I will attempt to create an awareness among the local auidience of the existence of an alternative form of local Chines music, other than pop and Xinyao. And that is Chinese Rock Music. As this form of music is relatively very new in the local Chinese music scene, I will play some of the music of these rock groups. At the same time, I will invite them to my program to talk about their music and their compositions, about this form of music generally in the local scene, its birth and growth, and prospects, the local audience s perception of Chinese Rock Music, and comparing local Chinese Rock Music with that of China, Hong Kong and Taiwan. All in all, my aim is to expose local audience to an alternative form of local Chinese music.